The Connotations Of The Term Emotion In Arabic Critical Studies/ دلالات مصطلح العاطفة في الدراسات النقدية العربية - Tariq Muhammad AlMugim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
A review of classical Arabic lexicons shows that the term ʿāṭifah (emotion) originally conveyed meanings of tenderness and care. In the modern period, however, its semantic scope expanded to encompass a broader range of affective states, including anger, resentment, fear, and other emotional responses. Thus, when we speak of the “emotion of the writer,” the term is not confined to notions of love and affection, but extends to all affective experiences a human being may undergo, such as anger and disgust. Classical Arab critics addressed poetic genres from an affective perspective by employing related terms and near-synonyms for emotion, such as maqāṣid (intentions), aghrāḍ (themes or purposes), and aḍrāb (types), among others. Contemporary Arab critics, in turn, were influenced by Western conceptualizations of emotion and by the expansion of its semantic and theoretical dimensions. They were also influenced by Western attempts to differentiate between emotion and feeling. By synthesizing the Arab critical heritage with Western scholarship, Arab critics were able to employ the concept of emotion in developing literary criticism. Theorist-critics sought to define the role and status of emotion within the literary work, and subsequent scholars endeavored to apply these theoretical insights to detailed textual analyses. They identified the types of emotions present in literary texts, their classifications, the lexical and stylistic markers that signal them, as well as the rhetorical techniques and strategies that implicitly convey affect. Such critical concepts cannot be isolated from psychological studies, which may assist both critics and authors in understanding the affective and emotional dynamics of the human psyche. These studies have arguably contributed to clarifying ambiguities surrounding authors’ emotions and feelings, especially since many literary expressions and imaginative constructs that signal affect cannot be adequately interpreted solely from a literary or aesthetic perspective; rather, they must be supported by psychological and human sciences.